Macintosh revisited: posthumanism, critique, and close observing in Ulysses. Issue 2 (1st February 2022) - Ramey, James
ABSTRACT: From the early days of Joyce criticism, the identity of the macintosh man in Ulysses has enthralled critics. Although more than a dozen solutions have been proposed over the century since the novel's publication, an assumption has long held sway that Joyce intended the figure to be a riddle without a solution. However, one solution from the 'precritique' period of literary criticism happens to be extremely difficult to refute. If it is the case that we are entering a 'postcritique' era, as Rita Felski and others have advocated, is it possible that arguments about the existence of riddle-systems can be reappraised and reimagined in the current context? This article will experiment with Niklas Luhmann's systems theory to propose a posthumanist methodology for close observing of literary texts. Close observing, over and against close reading, is possible only for what Luhmann describes as observers of the second and third orders. The article demonstrates, on the one hand, that posthumanism offers potent new forms for engaging with texts, and on the other, that the deployment of the macintosh riddle-system in Ulysses exemplifies one way Joyce's art and thought is already paradigmatic of posthumanism.